Twelve-Year-Old Girl with Primary Biliary Cirrhosis - Ivana Kitic; Aleksandra Boskovic; Ivica Stankovic; Dragan Prokic (Case Reports in Pediatrics)
Primary biliary cirrhosis (PBC) is a slowly progressive cholestatic liver disease of autoimmune etiology. The initial presentation of PBC is varies from asymptomatic, abnormal liver biochemical tests to overt cirrhosis. Unlike other autoimmune liver diseases, PBC has rarely been reported in childhood. We report a case of primary biliary cirrhosis in a 12-year-old girl. In addition to characteristic histology features, strongly positive antimitochondrial antibodies, increased liver enzyme levels, increased serum quantitative immunoglobulin M levels, and cholestasis were discovered. She had been treated with ursodeoxycholic acid. In the world literature, we found only few pediatric patients of primary biliary cirrhosis. Aetiology, pathogenesis, the long-term natural history, and prognosis remain obscure. Due to increased awareness of early-onset PBC, rather than typical older ones, further pediatric cases may be discovered.